Identification of WRKY transcription factors in Ipomoea pes-caprae and functional role of IpWRKY16 in sweet potato salt stress response - Jiaying Wu; Yiren Su; Zhiyuan Pan; Yiming Wang; Yongjing Zhang; Ludan Li; Jihong Jiang; Xiaoying Cao (BMC Plant Biology)
Abstract Background WRKY transcription factors are plant-specific and play essential roles in growth, development, and stress responses, including reactions to salt, drought, and cold. Despite their significance, the WRKY genes in the wild sweet potato ancestor, Ipomoea pes-caprae, remain unexplored. Results In this study, 65 WRKY genes were identified in the I. pes-caprae transcriptomic data. A phylogenetic tree incorporating Arabidopsis thaliana and Ipomoea batatas revealed seven major groups, each characterized by conserved gene structural features. Transcriptome data of I. pes-caprae under salt stress conditions identified 17 highly expressed WRKY genes, whose promoter regions contain cis-acting elements associated with plant growth, stress responses, and hormone signaling. Further analysis revealed that the 17 IpWRKY genes exhibited differential expression patterns under various abiotic stresses, suggesting their potential roles in specific stress responses. The gene IpWRKY16 was significantly up-expressed under salt stress, drought, salicylic acid (SA), and abscisic acid (ABA) treatments. Subcellular localization analysis confirmed that IpWRKY16 is located in the nucleus. Under salt stress, IpWRKY16 overexpressing roots showed high activity in superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and low content in malondialdehyde (MDA). Using non-invasive micro-test technology (NMT), a significant efflux of Na+ was observed in the elongation zones of sweet potato adventitious roots that overexpressed IpWRKY16. Quantitative reverse transcription PCR (qRT-PCR) revealed that several ion transporter genes were responsive to IpWRKY16 expression, with IbSOS3, IbAHA4-1, and IbAHA4-2 showing the highest expression levels. We hypothesize that IpWRKY16 responds to salt stress by forming a complex regulatory network involving these key genes. Conclusions This study provides a foundational understanding of WRKY transcription factors in I. pes-caprae, offering insights into their potential role in enhancing salt-tolerance in sweet potato. Our findings contribute valuable genetic knowledge that could aid in the molecular breeding of stress-resilient sweet potato varieties.